Privacy and Security on RFID Technology: Exploring the Challenges and Solutions in Privacy and Security of RFID Technology (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper surveys recent technical researches on the problems of Privacy and Security for various programs in radio frequency identity (RFID). Most RFID gadget attempt to lay out a high stage protection, however not all of the RFID applications need it. The fee will boom if the Privacy and Security simultaneously improve, for that reason, the way to balance the problems is critical. This paper gives an insight into the Privacy and Security requirements for RFID applications by means of the commercial methods. We will discuss and evaluate privacy and protection in various cases. The effects of our surveys are beneficial for security engineers, who're accountable for the design and development in RFID.